Evaluation of Changes in Macular Perfusion Detected by Optical Coherence Tomography Angiography following 3 Intravitreal Monthly Bevacizumab Injections for Diabetic Macular Edema in the IMPACT Study - Ayman G. Elnahry; Ahmed A. Abdel-Kader; Karim A. Raafat; Khaled Elrakhawy (Journal of Ophthalmology)
Objective. To evaluate macular perfusion changes following intravitreal bevacizumab injections for diabetic macular edema (DME) using spectral domain optical coherence tomography angiography (SD-OCTA). Methods. This study was a prospective noncomparative interventional case series. Treatment naïve patients with DME underwent full ophthalmological examination and SD-OCTA scanning at baseline and after 3 intravitreal bevacizumab injections. Both the 6 × 6 and 3 × 3 mm macular scan protocols were used. Pretreatment and posttreatment OCTA images were automatically aligned using a commercially available retina alignment software (i2k Align Retina software); then the fractal dimension (FD), vascular density (VD), and skeleton VD changes were obtained at the full retinal thickness (Full) and superficial (SCP) and deep (DCP) capillary plexuses after processing images using a semiautomated program. The foveal avascular zone (FAZ) was manually measured and FD was calculated using the FracLac plugin of ImageJ. Results. Forty eyes of 26 patients were included. Following injections, there were an 8.1% increase in FAZ, 1.3% decrease in FD-Full and FD-SCP, 1.9% decrease in FD-DCP, 8% decrease in VD-Full, 9.1% decrease in VD-SCP, 10.6% decrease in VD-DCP, 13.3% decrease in skeleton VD-Full, 12.5% decrease in skeleton VD-SCP, and 16.3% decrease in skeleton VD-DCP in the 6 × 6 mm macular area and a 2.6% decrease in FD-Full, 3.4% decrease in FD-SCP, 11.5% decrease in VD-Full, 14.3% decrease in VD-SCP, and 25.1% decrease in skeleton VD-SCP in the 3 × 3 mm macular area which were all statistically significant p<0.05. Using univariate and multivariate analysis, the pretreatment FD, VD, and skeleton VD at each capillary layer significantly negatively correlated with the change in FD, VD, and skeleton VD at the corresponding capillary layer, respectively p<0.05. Conclusion. OCTA is a useful noninvasive tool for quantitative evaluation of macular perfusion changes following DME treatment. This trial is registered with NCT03246152.